2016
DOI: 10.1136/oemed-2016-103747
|View full text |Cite
|
Sign up to set email alerts
|

Shift work, job strain and changes in the body mass index among women: a prospective study

Abstract: Job strain and rotating night shift work have independent contributions to weight gain. Reducing job strain and supporting night shift workers are both important intervention goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
0
17
0
5
Order By: Relevance
“…It has been reported that workplace stress can increase the likelihood of fast eating 11 . Job stress is often accompanied by a change in eating behaviors including fast eating, eating beyond the point of a full stomach 12 , surrogate meals or overeating, and increased calorie intake 13 , which were speculated in causes of obesity in Japanese men and women 14 . In Japan, men were more likely to be employed on full-time than women; 22.78 million men vs 10.78 million women in full-time employment (http://www.stat.go.jp/english/index.html).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that workplace stress can increase the likelihood of fast eating 11 . Job stress is often accompanied by a change in eating behaviors including fast eating, eating beyond the point of a full stomach 12 , surrogate meals or overeating, and increased calorie intake 13 , which were speculated in causes of obesity in Japanese men and women 14 . In Japan, men were more likely to be employed on full-time than women; 22.78 million men vs 10.78 million women in full-time employment (http://www.stat.go.jp/english/index.html).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of the dietary characteristics of shift workers found that that while diet quality does not differ between shift workers and those working regular hours, doing night shifts was associated with higher energy intake (36). Fujishiro et al (34) examined the cumulative exposure to rotating night shifts among more than 50 000 women from the Nurses’ Health Study II, and demonstrated an independent contribution of night shift work to weight gain. The development of workplace lifestyle interventions specifically for shift workers is an emerging field (33).…”
Section: Shift Work and Health Risksmentioning
confidence: 99%
“…On the other hand, some studies have confirmed the negative influence of unemployment on life satisfaction and self-assessed health status [8,9]. Furthermore, specific elements of work such as rotating shift work correlate with a decreased quality of life and are associated with an increase in coronary heart disease risk and independently contributes to weight gain [9,10]. Moreover, occupational stress leads to some problems, for instance, chronic fatigue syndrome or burnout [11,12,13].…”
Section: Introductionmentioning
confidence: 99%